2009
DOI: 10.1055/s-0029-1238319
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism within the Fructosamine-3-kinase Gene is Associated with HbA1c Levels and the Onset of Type 2 Diabetes Mellitus

Abstract: We conclude that the G900C polymorphism associates with the level of HbA (1c) and the onset of the disease, but not with either of the diabetic microvascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…Moreover, FN3K SNPs associated significantly with typical aspects of diabetes have been described [28][29][30]. All this evidence reinforces the hypothesis that the combination of particular variants in the promoter and exon regions could turn into enhanced or reduced expression of other enzymes or regulator factors involved into deglycation.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, FN3K SNPs associated significantly with typical aspects of diabetes have been described [28][29][30]. All this evidence reinforces the hypothesis that the combination of particular variants in the promoter and exon regions could turn into enhanced or reduced expression of other enzymes or regulator factors involved into deglycation.…”
Section: Discussionsupporting
confidence: 54%
“…However, they failed to detect a correlation between FN3K SNPs and HbA 1c levels [27]. Then, the group of Mohás analyzed a large cohort of type 2 diabetic (T2DM) subjects (859 T2DM and 265 controls) for the presence of the polymorphism c.900C/G (rs1056534) of the FN3K gene [28]. They found that the C allele of rs1056534 was coupled with lower HbA 1c concentration and with a later onset of type 2 diabetes.…”
Section: Genetics: Results From Presented Studiesmentioning
confidence: 99%
“…Of those we found marginal association of rs1056534 located in exon 6 with DN progression. This SNP was previously associated with HbA1C and onset of diabetes, but not with any type of diabetic microvascular complications [15]. The most thorough analysis was performed for genetic variation in TKT, an important enzyme of the non-oxidative branch of PPP with proven increase of activity in diabetes [5].…”
Section: Discussionmentioning
confidence: 99%
“…Protein glycation is a nonenzymatic reaction dependent on glucose concentrations, but intracellular enzymatic deglycation of proteins has also been identified (10). The key deglycating enzyme, fructosamine-3-kinase, has isoforms and a genetic polymorphism suggested to influence HbA 1c variability, but any impact on HbA 1c glycation is unknown; although it seems unlikely that glycated HbA 1c is a substrate for this enzyme since it has been shown that there is no evidence that it plays any role in HbA 1c deglycation at the relevant glycation site (11,12). To add to the potential for a spurious generation of a G-gap, many factors, including variability in protein turnover and obesity, may affect fructosamine estimation (1,13,14).…”
mentioning
confidence: 99%